Multiple verrucous lesions of the feet in Waldenström macroglobulinaemia. (1st January 2018) - Naito, R.; Koga, K.; Masaki, M.; Fujii, N.; Ito, K.; Koga, M.; Imafuku, S.
Abstract: Click here for the corresponding questions to this CME article.